Exploring Lexical and Contextual Meaning in Happier Than Ever Album by Billie Eilish - Yastanti, Unpris; Oktaviani, Allya Legina; Adi, Wiruma Titian; Yuskar, Bobby Octavia; Manar, Marsandi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study aims to identify both lexical and contextual meanings found in song lyrics, and to determine which type of meaning is more dominant in Billie Eilish’s album Happier Than Ever. The data source for this research is the lyrics from the album, analyzed using lexical and contextual meaning theories. This research employs a descriptive qualitative method and focuses on five selected songs: Getting Older, I Didn’t Change My Number, Billie Bossa Nova, My Future, and Not My Responsibility.” The analysis is based on the theories of lexical and contextual meaning proposed by Parera and Chaer. The results reveal: 1) 16 lexical meanings are identified, consisting of two types; synonymy and polysemy. Moreover, 28 contextual meanings were found, categorized into four types: mood context, situational context, time context, and purpose context 2)The analysis concludes that contextual meaning is more dominant than lexical meaning in the lyrics. This study contributes to linguistics and cultural analysis by showing how popular music uses language to express and reflect social, emotional, and individual experiences, highlighting the close relationship between language and culture.